EKSPERIMENTASI MODEL PEMBELAJARAN TIPE PROBLEM POSING DAN MODEL PEMBELAJARAN TIPE PROBLEM SOLVING DITINJAU DARI GAYA BELAJAR SISWA SMP NEGERI KELAS VIII KOTA SURAKARTA - Aprisetyani, Giant; Budiyono, Budiyono; Subanti, Sri (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objectives of this research were to investigate: (1) which learning model of the Problem Posing, Problem Solving, and Direct Instruction results in a better learning achievement in Mathematics;  (2) which students of those with the visual learning style, those with the auditorial learning style, and those with the kinesthetic learning style have a better learning achievement in Mathematics; (3) in each learning model, which learning style of the visual learning style, the auditory learning style, and the kinesthetic learning style results in a better learning achievement in Mathematics; (4) in each learning style, which learning model of the the Problem Posing, the Problem Solvingand the Direct Instruction results in a better learning achievement in Mathematics.This research used the quasi experimental research with the factorial design of 3 x 3. The population of the research was all of the students in Grade VIII of State Junior Secondary Schools in Surakarta in Academic Year 2013/2014. The samples of the research were taken by using the stratified cluster random sampling technique. The samples consisted of three schools, namely: State Primary School 3, State Primary School of Surakarta, State Primary School 10 of Surakarta, and State Primary School21 of Surakarta. The proposed hypotheses of the research were tested by using the two-way analysis of variance (ANAVA) with unbalanced cells with the factorial design of 3 x 3. The results of the research are as follows: (1) the students instructed with the Problem Solving model have a better learning  achievement in Mathematics than those instructed with the Problem Posing type learning model and those instructed with the Direct Instruction, and the students instructed with the Problem Posing type learning model have a better learning achievement in Mathematics than those instructed with the Direct Instruction;  (2) the students with the visual learning style have a better  learning achievement in Mathematics than those with the auditory learning style  and those with the kinesthetic learning style, and the students with the auditory learning style have a better learning achievement in Mathematics than those with the kinesthetic learning style; (3a) in the Problem-Posing type learning model, the learning achievement in Mathematics of the students with the visual learning style is the same as that of the students with the auditory learning style, and the learning achievement in Mathematics of the students with the auditory learning style  is the same as that of the students with the kinesthetic learning style, but the learning achievement in Mathematics of the students with the visual learning style is better than that of the students with the kinesthetic learning style, (3b) in the Problem Solving type learning model, the learning achievement in Mathematics of the students with the visual learning style is the same as that of the students with the auditory learning style, the learning achievement in Mathematics of the students with the auditory learning style is the same as that of the students with the kinesthetic learning style, but the learning achievement in Mathematics of the students with the visual learning style is better than that of the students with the kinesthetic learning style, and (3c) in the  Direct Instruction, the learning achievement in Mathematics of the students with the visual learning style is the same as that of the students with the auditory learning style and that of the students with the kinesthetic learning style; and (4a)  in the students with visual learning style, the learning achievement in Mathematics of the students exposed to the problem possing type learning model is the same as that of the students exposed to the problem solving type learning model, the learning achievement in Mathematics of the students exposed to problem possing type learning model is better than that of the students exposed to the direct instruction, and the learning achievement in Mathematics of the students exposed to the problem solving is better than that of the students exposed to direct instruction, (4b) in the students with the auditory learning style, the learning achievement in Mathematics of the students exposed to the problem posing type learning model is the same as that of the students exposed to the problem solving type learning model and that of the students exposed to the direct instruction, and (4c) in the students with the kinesthetic learning style, the learning achievement in Mathematics of the students exposed to the problem possing type learning model is the same as that of the students exposed to the problem solving type learning model, and that of the students exposed to the learning instruction.Keywords:  Problem Posing, Problem Solving, Direct Instruction, learning styles, and learning achievement in Mathematics.